The Relationship Between Nail Hygiene and the Incidence of Intestinal Parasite Infections (Intestinal Parasites) in Scavengers at Final Disposal Sites (TPA) Terjun Village, Medan Marelan District, Medan - Hutagaol, Crisny; Siahaan, Lambok; Carolina, Yoan; Haryani, Adelina; Sitanggang, Maria; Shinaya, Shinaya (Universitas Syiah Kuala, 2025)
Background. Intestinal parasitic infections are a global problem in humans, especially in developing countries. Indonesia has an intestinal parasitic infection prevalence rate of 45-65%. Intestinal parasitic infections are caused by helminths, namely Ascaris lumbricoides, Hookworms, Trichuris trichiura, and protozoa. The mode of transmission is ingestion of eggs or other infective forms. Nails are the body part that transmits infective forms of intestinal parasites orally. Scavengers work to sort garbage and have contact with the ground with a high risk of intestinal parasite infection. Objective. To determine the relationship between nail hygiene and the incidence of intestinal parasitic infections in waste pickers at Terjun landfill. Methods. Observational analytic research design with cross sectional method. Primary data was obtained from 121 waste pickers by interviewing based on questionnaires, collecting nails and feces in Terjun Village, Medan Marelan District. Samples were examined using a light microscope with 100x and 400x magnification at the Parasitology Laboratory, Faculty of Medicine, University of North Sumatra. Results. Four intestinal parasites were found in the nails and 18 intestinal parasites in the feces of scavengers. There were 95 people (78.5%) with healthy nails and 74 people (66.8%) with poor hand hygiene. Conclusion. There is a relationship between hand hygiene and nail health with a p value of 0.000. There is a relationship between nail hygiene and infection